Efficacy of Exenatide Administered Twice Daily in Body Mass Index Reduction in Patients with Type 2 Diabetes Mellitus - Jie Zhang; Tong-Zhang Xian; Yu Teng; Xiuzhi Wang; Ming-Xiao Wu; Chen Li; Weihao Wang; Fuli Man; Xianbo Zhang; Xiaoxia Wang; Li-Xin Guo (International Journal of Clinical Practice)
Background. Exenatide is a glucagon-like peptide-1 receptor agonist that can reduce body weight. This study aimed to determine the efficacy of exenatide on body mass index (BMI) reduction in patients with type 2 diabetes mellitus (T2DM) with differing baseline body weight, blood glucose, and atherosclerotic status and to determine if there is a correlation between BMI reduction and cardiometabolic indices in these patients. Methods. This retrospective cohort study used data from our randomized controlled trial. A total of 27 T2DM patients treated with combination therapy of exenatide twice daily and metformin for 52 weeks were included. The primary endpoint was a change in the BMI from the baseline to week 52. The secondary endpoint was a correlation between BMI reduction and cardiometabolic indices. Findings. The BMIs of overweight and obesity patients and those with glycated hemoglobin (HbA1c) ≥ 9% significantly decreased −1.42 ± 1.48 kg/m2P=0.015 and −0.87 ± 0.93 kg/m2P=0.003, respectively, at the baseline after 52 weeks of treatment. There was no reduction in BMI in patients with normal weight, HbA1c <9%, the nonatherosclerosis group, and the atherosclerosis group. The decrease in BMI was positively correlated with changes in blood glucose, high-sensitivity C-reactive protein (hsCRP), and systolic blood pressure (SBP). Conclusion. BMI scores improved after exenatide treatment for 52 weeks in T2DM patients. Weight loss was affected by baseline body weight and blood glucose level. In addition, BMI reduction from the baseline to 52 weeks was positively correlated with baseline HbA1c, hsCRP, and SBP. Trial Registration. Chinese Clinical Trial Registry (ChiCTR-1800015658).